IMPROVING MECHANISMS FOR ATTRACTING GREENINVESTMENTS IN THE ECONOMY OF UZBEKISTAN (World Economics and Finance Bulletin, 2026)
This study explores the mechanisms for attracting green investments in the economy of Uzbekistan in the context of sustainable development and environmental transformation. The growing importance of environmentally responsible investment has become a key factor in ensuring long-term economic stability, reducing ecological risks, and enhancing energy efficiency. Special attention is given to the role of government incentives, regulatory instruments, and financial market development in promoting green investment activities. The study also examines international best practices in green finance, including the use of green bonds, public-private partnerships, and ESG (Environmental, Social, and Governance) standards, adapting them to the national economic context. Based on analytical and comparative approaches, the research proposes a set of recommendations aimed at improving the investment climate, strengthening financial infrastructure, and increasing the attractiveness of Uzbekistan for sustainable investments. The findings highlight that enhancing transparency, developing specialized financial instruments, and integrating digital technologies into investment processes can significantly boost green investment flows and contribute to the achievement of sustainable economic growth.
Keywords: Green investment; sustainable development; green finance